Negative Effect of Camu-Camu (Myrciaria dubia) Despite High Vitamin C Content on Iron Bioavailability, Using a Caco-2 Cell Model - Nemirovsky, Yael; Zavaleta, Nelly; Villanueva, Maria; Armah, Seth; Imán Correa, Sixto Alfredo; Reddy, Manju (Polish Academy Sciences. Institute of Animal Reproduction and Food Research, 2017)
[EN] It is well known that vitamin C is an important enhancer of nonheme iron bioavailability due to its high reducing capacity. Camu-camu, a fruit that grows in the jungle of Peru, contains high amount of vitamin C (2,780 mg per 100 g). In this study, we investigated the effect of camu-camu on nonheme iron bioavailability from two different meals (rice with lentils and wheat flour porridge) using an in vitro Caco-2 cell model. These two meals were treated with three different camu-camu juice concentrations (C0 = 0 g, C1 = typical consumption, and C2 = 3X typical consumption). The results showed that camu-camu reduced rather than enhanced nonheme iron bioavailability. The inhibiting trend was significant (p<0.0001) in the wheat flour porridge (from 124 to 91 and 35 μg ferritin/μg protein, for C0, C1 and C2, respectively). With the rice with lentils, there was no significant effect of camu-camu due to the high polyphenols and phytate contents of the meal. Relative bioavailability values obtained showed significant decrease with increasing camu-camu juice concentration for both meals. As expected, the ascorbic acid added to the meals at a concentration equivalent to that present in C2, had no effect on bioavailability with rice meal but increased significantly with wheat flour meal. The findings of this study suggest that camu-camu, in the traditional way of preparation, may significantly reduce nonheme iron bioavailability because of its high polyphenol content which overrides the beneficial effect of its high ascorbic acid content.